THE EFFECT OF MINIMUM WAGES, UNEMPLOYMENT RATE, AND INFLATION ON POVERTY IN INDONESIA - Nariyah Agustiani, Miftah; Adilia, Sabina; Rosa, Erica Della; Panorama, Maya (Jurnal Manajemen, Akuntansi, Ekonomi, 2023)
One of the problems that are rife in Indonesia is the problem of poverty. Many factors influence the causes of poverty, such as minimum wages that do not meet the needs of life, uneven employment opportunities, and rising inflation. In this study, we discuss how these factors affect poverty rates in Indonesia.